Pressure-induced unfolding of lysozyme in aqueous guanidinium chloride solution. - Sasahara, K. (Cold Spring Harbor Laboratory Press, 1999)
The pressure-induced unfolding of lysozyme was investigated in an aqueous guanidinium chloride solution by means of ultraviolet spectroscopy. Assuming a two-state transition model, volume changes were calculated from the slope of free energy vs. pressure plots over a temperature range of 10 to 60 degrees C. Between 25 and 60 degrees C, almost constant volume changes were observed in the transition region, which was reflected in almost identical slopes of the free energy change vs. pressure plots. On the other hand, the different slopes were observed in the pressure dependence of free energy change at temperatures lower than 25 degrees C. These data were interpreted as suggesting that a two-state model is not appropriate at low temperature, but instead one or more intermediates are present under these conditions. The volume changes for unfolding became less negative at temperatures higher than 25 degrees C.